Heat shock pretreatment induced cadmium resistance in the nematode Caenorhabditis elegans is depend on transcription factors DAF-16 and HSF-1. (June 2020) - Wang, Shunchang; You, Mu; Wang, Chengrun; Zhang, Yuecheng; Fan, Caiqi; Yan, Shoubao
Abstract: Cadmium (Cd) exposure poses a serious environmental problem due to the metal's bioaccumulation and difficult to eliminate from body. Understanding the mechanisms of Cd detoxification and resistance can provide insights into methods to protect against the damaging effects of the heavy metal. In the present study, we found that heat shock (HS) pretreatment increased Cd resistance of the nematode Caenorhabditis elegans by reducing the bagging phenotype and protecting the integrity of the intestinal barrier. HS pretreatment increased the expression of heat shock protein-16.2 (HSP-16.2) prior to Cd exposure, and HS-induced Cd resistance was absent in worms with hsp-16.2 loss-of-function mutation. Worm strain with daf-2(e1370) mutation presented enhanced HS-induced Cd resistance, which was eliminated in worm strains of daf-16(mu86) and hsf-1(sy441) . HS pretreatment increased DAF-16 nuclear localization and HSF-1 granule formation prior to Cd exposure. DAF-16 and HSF-1 was essential in reducing bagging formation and protecting the integrity of intestinal barrier after HS pretreatment. In conclusion, the present study demonstrated that HS-induced Cd resistance in C. elegans is regulated by the DAF-16/FOXO and HSF-1 pathways through regulation of HSP-16.2 expression. Graphical abstract: Image 1 Highlights: Heat shock pretreatment increased cadmium resistance in C. elegans. HS pretreatment reduced bagging formation and intestine barrier leaking. HS pretreatment enhanced the expression of HSP-16.2 prior to cadmium exposure. DAF-16 and HSF-1 played essential roles on HS-induced cadmium resistance. Abstract : Transient heat shock pretreatment increased Cd resistance in C. elegans is dependent on the transcription factors DAF-16 and HSF-1.